2017
DOI: 10.20518/tjph.341158
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancies, induced abortions and risk factors in women admitted to hospitals due to birth or abortion in Hatay

Abstract: Objective: The aim of this study is to determine the frequency of unintended pregnancies, induced abortions and associated risk factors in women who have been admitted to hospitals in Hatay. Method: The subjects of this cross-sectional study were women who had been admitted to hospitals for the purposes of delivery or abortion, during a month-long period. A structured questionnaire was taken by 635 women. Unintended pregnancy was dependent variable. The independent variables were: age, husband's age, civil sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The partner's working status and pregnancy are not expected to have a significant correlation with the odd ratio of husbands not working at 1.77. The results of this study are in line with the results of research in countries with a majority Muslim population such as Turkey (17,18) and Egypt (19). The possibility of insufficient husband's income influences men's decisions about pregnancy, which is generally the choice of men which also controls women's access to care, education and welfare.…”
Section: Couple's Working Statussupporting
confidence: 89%
“…The partner's working status and pregnancy are not expected to have a significant correlation with the odd ratio of husbands not working at 1.77. The results of this study are in line with the results of research in countries with a majority Muslim population such as Turkey (17,18) and Egypt (19). The possibility of insufficient husband's income influences men's decisions about pregnancy, which is generally the choice of men which also controls women's access to care, education and welfare.…”
Section: Couple's Working Statussupporting
confidence: 89%
“…In another study conducted on married women aged 18-49 years, the rate of unwanted pregnancies was 26.1% and 26.1% of these women had 2 and 5.8% had 4 or more unwanted pregnancies (15). In a study conducted on women who applied to hospitals, it was found that unwanted pregnancies were 15% and this rate was reported to be higher in women with low educational level and in women whose husbands were unemployed (16). The rate of unwanted pregnancies is 40% worldwide (2).…”
Section: Discussionmentioning
confidence: 97%